The Taste for Ethics - Coff, Christian. author. aut Link
XIX, 212 p.
Keywords: This book marks a new departure in ethics. In our culture ethics has first and foremost been a question of ‘the good life’ in relation to other people. Central to this ethic was friendship, inspired by Greek thought, and the caritas concept from the Judaeo-Christian tradition. But no early moral teaching discussed man’s relation to the origin of foodstuffs and the system that produced them; doubtless the question was of little interest since the production path was so short. Before industrialisation the production of food was easy to follow. As a rule that is no longer the case. The field of ethics must therefore be extended to cover responsibility for the production and choice of foodstuffs, and it is this food ethic that Christian Coff sets out to trace. In doing so he shows how the focus of ethics can be expanded from its concern for the good life with and for others to cover the good life in fair food production practices, and how not least through using our integrity orlife coherence we can reflect ethically, or caringly, about living organisms, ecological systems and our human identity. From the foreword by Dr. Peter Kemp, Professor of Philosophy at the Danish University of Education.